ENHANCEMENT OF THE SENSITIVITY AND SELECTIVITY OF THE VOLTAMMETRIC SENSOR FOR URIC ACID USING MOLECULARLY IMPRINTED POLYMER - Miratul Khasanah; Mudasir Mudasir; Agus Kuncaka; Eko Sugiharto; Ganden Supriyanto; Siti Wafiroh (Indonesian Journal of Chemistry, 2010)
The sensitivity and selectivity of voltammetric sensor for uric acid can be improved by modifying the working electrode using a polymer with a molecular template (molecularly imprinted polymer, MIP). Polymer and MIP was synthesized from methacrylic acid (MAA) as monomer, ethylene glycol dimethacrylic acid (EGDMA) as cross-linker, uric acid (UA) as template and the results were characterized by various methods. The poly-MAA formation was identified by a decrease in the intensity of infrared (IR) spectra at ~1540 cm-1 (C=C) and an increase at ~1700 cm-1 (C=O) compared to the IR spectra of the MAA and EGDMA. The SEM analysis showed that the cavity of polymer is small enough (~ 0.1 µm) and homogeneous. Establishment of MIP was carried out by extracting of the uric acid from the polymer network. The IR spectra of MIP exhibited the decrease in intensity at ~1700 cm-1 (C=O) compared to the non imprinted polymer (NIP). The data of BET analysis showed that polymer pore size increase slightly from 37.71 Å to 38.02 Å after the extraction process of uric acid from the polymer network. Its may be due to incomplete extraction of uric acid from the polymer network. Modifications of hanging mercury drop electrode using MIP made from MAA, EGDMA, and UA with a mole ratio of 1:3:1 produced a sensitive and selective voltammetric sensor for uric acid. The sensitivity obtained was 16.405 nA L/µg. The presence of ascorbic acid in equal concentration with uric acid decreased the current response of only 0.08%. Compared to HMDE electrode, the sensitivity and selectivity of the HMDE-MIP sensor enhanced about 100 and 700 times, respectively. The detection limit was found to be 5.94 x10-10 M.